A SHORT REVIEW ON: SULPHONAMIDES - AASTHA PAREEK; PRIYANKA RANI; D. KISHORE (International Journal of Pharma and Bio Sciences, 2013)
Sulfonamides/sul.fon.amides/ (sul-fon´ah-mÄ«d) are one of the organosulphur compounds containing the -SO2NH2 and/or -SO2NH- group(s). The sulfonamides or sulfa drugs competitively inhibit folic acid synthesis in micro-organisms and subsequently inhibit multiplication of bacteria but do not actively kill them. They have been used against most gram-positive and many gram-negative bacteria, some fungi, and certain protozoa. Medically important sulphonamides.